PENDIDIKAN HUKUM DI ERA TRANSISI DALAM NEGARA DEMOKRASI MENUJU INDONESIA BARU - Khaidir Anwar (Masalah-Masalah Hukum, 2011)
The Higher Law Education was started from senior high school level (Rechsschool), founded in 1908 during the Dutch colonial occupation. In 1924, law education was upgraded to university level which was called as "Rechtshogeschool". The paradigm of legal education is influenced by political change in governance implementation. In the colonial period, law education is intended only for practical purposes to fill certain positions in the law field. The Old Era continued this "tradition". Fundamental change occurred in the New Era, where laws serve as "tools of social engineering." In the year 1993, the curriculum of higher law education also has included "law skills", so that law school graduates "ready-made" to the business world. It is necessary to built the law education system which places Pancasila as the paradigm of jurisprudence, so that law education is executed through the integrity of understanding, producing and law implementation in a process of achieving justice and human happiness. It is time for law education to eliminate the law school graduates who are only oriented to purely law dogmatic and lacking the ability to abstract the social phenomena into the rules of law, thus many legal products are not in accordance with the law which life in society. Kata kunci: Pendidikan Hukum, EraTransisi, Indonesia Baru